Antimicrobial Activity of Nisin and Natamycin Incorporated Sodium Caseinate Extrusion‐Blown Films: A Comparative Study with Heat‐Pressed/Solution Cast Films. Issue 5 (6th April 2016) - Colak, Basak Yilin; Peynichou, Pierre; Galland, Sophie; Oulahal, Nadia; Prochazka, Frédéric; Degraeve, Pascal
Abstract: Antimicrobial edible films based on sodium caseinate, glycerol, and 2 food preservatives (nisin or natamycin) were prepared by classical thermomechanical processes. Food preservatives were compounded (at 65 °C for 2.5 min) with sodium caseinate in a twin‐screw extruder. Anti‐ Listeria activity assays revealed a partial inactivation of nisin following compounding. Thermoplastic pellets containing food preservatives were then used to manufacture films either by blown‐film extrusion process or by heat‐press. After 24 h of incubation on agar plates, the diameters of K. rhizophila growth inhibition zones around nisin‐incorporated films prepared by solution casting (control), extrusion blowing or heat pressing at 80 °C for 7 min of nisin‐containing pellets were 15.5 ± 0.9, 9.8 ± 0.2, and 8.6 ± 1.0 mm, respectively. Since heat‐pressing for 7 min at 80 °C of nisin‐incorporated pellets did not further inactivate nisin, this indicates that nisin inactivation during extrusion‐blowing was limited. Moreover, the lower diameter of the K. rhizophila growth inhibition zone around films prepared with nisin‐containing pellets compared to that observed around films directly prepared by solution casting confirms that nisin inactivation mainly occurred during the compounding step. Natamycin‐containing thermoplastic films inhibited Aspergillus niger growth; however, by contrast with nisin‐containing films, heat‐pressed films had higher inhibition zone diameters than blown films, therefore suggesting a partial inactivation of natamycin during extrusion‐blowing.